Chanakya Sutras and Arthasastra : The Gospels of Corporate Management for Modern Application - SIBA P. RATH (Dr. Chinmay Pandya, 2014)
The modern world corporate management and corporate governance is dominated by the theories and practices of American Management System, Japanese Management System and European Management System. Japanese Management techniques and practices are the champion concepts for any organization to follow in the context of quality management, production efficiency management, market competition management and above all human capital management etc. Japanese have established the dynamics of human capital and knowledge management as the best practices for any organization. The soundness of Japanese Management is derived from its treasure through revival of the Samurai System and traditional knowledge banks. European and American Management System are known for their contributions in the industrialization process of the world in the 19th and 20th century in the pre and post colonialism era. Indian oriental texts, gospels, practices, concepts, doctrines and arguments through logic are the sources of many Japanese management philosophies. India is a store house of pragmatic management and flawless applications in its ancient history phases. Oriental management texts and concepts need revival and rediscovery of the principles and system of applied management for use in the modern corporate world. Indian oriental system can and will create a system of its own as (IMS) Indian Management System like the Japanese. Proved and applied management of Chanakya during the Maurya Dynasty is historically evident as the best ever management practices India followed. Arthasastra and Chanakya Sutras are the two gospels of Indian management, enough to establish IMS the Indian management system for the modern corporate world of 21st century. These gospels applications are examined in the contemporary context for corporate use.